PENERAPAN MODEL PEMBELAJARAN NHT (NUMBERED HEAD TOGETHER) DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK SD - Sri Fitrianti; Andhin Dyas Fitriani; Asri Aulia Rachman (Jurnal Lensa Pendas, 2025)
The NHT (Numbered Head Together) learning model is one of the many cooperative learning models. The purpose of this study is to increase students' interest in learning through the application of the NHT learning model in the classroom. This study uses the Collaborative Classroom Action Research (CAR) method. The location of the study was carried out at SDN 037 Sabang, Bandung City with the research subjects being 30 class IV-B students. This collaborative classroom action research was carried out in two learning cycles. The data collection techniques used were observation and learning interest questionnaires according to four indicators of learning interest, such as feelings of pleasure, interest, attention, and student involvement. Based on the results of the collaborative classroom action study, there was a significant increase in learning interest after the implementation of the NHT learning model in the classroom. In cycle I, it reached 13 aspects, while in cycle II it increased to 15 aspects which were summarized in 4 indicators of learning interest. Thus, the application of the NHT learning model has proven effective in increasing the learning interest of class IV students. The application of the NHT learning model is one of the real actions of improvement in the learning process, so that changes and improvements need to continue to be made in order to increase students' interest in learning so that it has an impact on their learning outcomes.